Evaluation and Control, of Marine Pollution due to Land-Based Activities – A Preview of the Cyprus Case - Kathijotes, Nicholas (My University, 2010)
Most of marine pollution arises from land-based activities such as urban development and sewage disposal, agriculture, manufacture, transport, energy production and day-to-day domestic activity. Types of pollution include litter and oils, municipal wastewater, nutrients and sediments, radioactive waste, heavy metals and persistent organic pollutants. Once in the marine environment, the pollutants are absorbed by marine life, settle as sediments on sea bed, or follow dispersion. The pollutants pay no attention to national maritime boundaries or the sensitivity of the ecosystems they impact upon. The Mediterranean is a sensitive enclosed area with millions of people living in its coastal cities. This preview focuses on the southern coast of Cyprus, where the city of Limassol is located, in terms of the above mentioned hazards, with suggestions as to measures and practices to be taken in the direction of a model ecological city, based on an integrated coastal zone management practice. Wastewater reuse as a sustainable resource is linked to this study.
Keywords: coastal policy; nitrates; phosphates; marine pollution